Expansão do ensino superior e a política de assistência estudantil: análise a partir da percepção dos discentes assistidos na UFPB - Sousa, Amanda de Aquino (2021)
The expansion of higher education in Brazil, in the last two decades, has generated several educational policies, such as the Expand program and the Federal Universities Restructuring and Expansion Program - REUNI. The need to consolidate a policy aimed at student assistance became more evident from this expansion, as it is necessary to guarantee the permanence and enable the training of students with quality. In order to meet the demands of student assistance, in 2007, the National Student Assistance Program (PNAES) was created. The present research had as general objective to analyze the policy of student assistance at UFPB, in the context of the expansion of higher education, from the perception of the assisted students. This study is based on Mancebo (2015) and Ristoff (2016) who contextualized the expansion of higher education and access democratization policies; Chauí (1999) and Santos (2010) helped us to understand the influence of neoliberalism on education; Imperatori (2017), Kowaski (2012), supported us in the discussion of student assistance policy in Brazil. Barbosa (2009), Macedo (2017) and Silveira (2019) brought data about the reality of student assistance at UFPB. The research is inserted in a qualitative approach of bibliographic and documentary nature, in order to elucidate the context in which public policies for the expansion of higher education are inserted, to know the actions of student assistance in Brazil and how it is developed at UFPB. For data collection, we resorted to a field research through a questionnaire and participant observation, to know the student assistance provided by PRAPE/UFPB from the perspective of students and, based on it, to propose actions for its improvement. Data analysis was performed from Bardin's (2016) studies on content analysis. The results obtained show that the student assistance programs developed by PRAPE/UFPB have great relevance for the permanence of students in a condition of social vulnerability. The research subjects claim that the actions developed by student assistance programs strongly collaborate with their academic permanence, but they also point to the need to expand existing vacancies, faster selection processes, creation of new grants, improvement in the means of communication and disclosure of information, as well as readjustment in the amounts of aid.